Decolonization of Petroleum Education and Training in the Indonesian Oil Industry, 1950-1968 - Farabi Fakih (Universitas Gadjah Mada, 2021)
The article explores the decolonization of education within the Indonesian petroleum industry. The Netherlands Indies had one of the largest petroleum industries in the world with many major petroleum players involved. Despite this there was a lack of investment in training and schooling of engineers and workers in the Netherlands Indies. The article showed that the development of training and tertiary education in the 1950s was conducted by both the major oil companies and Indonesian government which invested in creating vocational training schools and university departments to meet industry needs. This development allowed for the creation of a government-run national education and research institute based in Java. The article shows that the role of the oil companies was still indispensable for the decolonization gap before the development of state-owned education institutes and the inclusion of Indonesian participation in the industry during the 1950s and 1960s. The active participation of the foreign oil industry in the Indonesianization of the industry was part of its ‘exceptionalism’ and the specific role oil played in the Indonesian economy.